Assessment by Multivariate Analysis of Groundwater between Low and High Tides Interactions in East Coast of Terengganu - Juahir, Hafizan; Barzani Gasim, Muhammad; Khairul Amri Kamarudin, Mohd.; Azid, Azman; Hairoma, Norsyuhada; Hafiz Md Saad, Muhammad; Mokhtar, Mazlin (International Journal of Engineering and Technology, 2018)
World sea level rise has an effect in the rise on high and low tides levels in coastal areas of Terengganu. Because of that, as many as 13 groundwater represented of well that located close to Terengganu coastline were sampled and analyzed. Samplings were conducted for the wet and dry seasons and also for the high and low tides at the same sampling wells to identify the variation of groundwater quality temporally. A Global Positioning System (GPS) was used to locate the exact coordinates of each sampling well. Nineteen physico-chemical parameters were analyzed from groundwater samples. Principal Component Analysis (PCA) was adopted to observe the contrast of the compositional pattern among the variables and to recognize the factors that influence the parameters as an input to define water intrusion. Hierarchical Agglomerative Clustering Analysis (HACA) is performed on data to group the sampling wells into a few clusters. The results show that from nineteen parameters only five has strong positive loading; EC (0.99), TDS (0.99), chloride (0.99), sulphate (0.92) and salinity (0.99) during high and low tides. The difference are BOD and DO have strong positive loading during low tide while turbidity and TSS were strong positive loading during high tide.Â Â